Developing a Model to Select Indicator Species Based on Individual Species’ Contributions to Biodiversity - Ta-Jen Chu; Yi-Jia Shih; Chun-Han Shih; Jia-Qiao Wang; Liang-Min Huang; Shu-Chen Tsai (Applied Sciences, 2022)
In both ecological research and engineering, the selection of indicator species is crucial. Biodiversity has always been an important policy objective for ecologists and environmental managers. Based on this target requirement, we developed a method that reveals the individual contributions of species to biodiversity to quantitatively identify indicator species for selection during environmental monitoring. The Siangshan Wetland in Hsinchu, Taiwan, was selected as an application case. The spread of mangroves not only changed the original habitat composition and function of benthic organisms in wetlands, but also led to problems such as estuary filling, flooding, and black mosquito breeding. Therefore, a large-scale mangrove removal project was undertaken by the Hsinchu City Government from October 2015 to March 2016. In this study, the biological effects of mangrove removal on benthic organisms and adjacent habitats were investigated from October 2015 to September 2016. According to biodiversity contribution algorithms, we identified five indicator species, namely, Mictyris brevidactylus, Macrophthalmus banzai, Uca arcuata, U. lacteal, and U. borealis. These indicator species had the most prominent biodiversity contribution, and they provided direct evidence of the beneficial effect of mangrove removal for wetland restoration. After mangrove deforestation, tidal flat species returned to their original habitats, and their related densities increased significantly in mangrove removal areas. Improving our understanding of the relationships between biodiversity and indicator species is crucial for the development of coastal management processes. Mangrove removal can be confirmed as an appropriate habitat rehabilitation strategy for benthic organisms. Consequently, these indicator species and the results obtained can provide valuable ecological information for those involved in coastal management or other officials seeking to control the spread of mangroves.